Open Neck Lift: Surgical Technique and A Clinical Classification for Cervical Rejuvenation - Khan, Muhammad Adil Abbas; Ma, Yangmyung; Dargan, Dallan; Kelemen, Noemi; Bhatti, Dujanah; Riaz, Armaan; Riaz, Muhammad (Facial Plastic Surgery, 2024)
Careful evaluation of the neck and its relationship to the lower third of the face is fundamental to provide appropriate recommendations for procedures. The authors propose a modified Baker “clinical” classification as a more reliable and reproducible evaluative basis for the treatment of the aging neck. A total of 450 patients underwent procedures for cervical rejuvenation between December 2012 and December 2022 by the senior author. These included 9 cases of neck liposuction, 6 isolated neck lifts, 15 minimal access cranial suspension face lifts, 94 face lifts with open neck lifts, and 326 extended R-face and neck lifts. The male-to-female ratio was 1:20. The mean patient age was 59.1 years and the mean follow-up was 14 months (range 11.5–20 months). From the data, a modified Baker clinical classification for the aging neck was formulated along with recommendations for possible solutions. Ninety-four percent of the patients expressed high satisfaction on the Owsley Facelift Satisfaction Survey at 1-year follow-up. The complication rate was 1.78% (8 patients), including 1 hematoma, 1 skin edge necrosis (1 cm), 1 slow healing site (postauricular), 3 limited postauricular/earlobe scar revisions, and 2 mild contour irregularities. Cervical rejuvenation can be achieved by a spectrum of interventions and approaches. A comprehensive preoperative assessment and a clinical neck lift classification are the keys to selecting the correct surgical technique for achieving reliable and consistent results. The authors propose a pragmatic approach for both isolated and integrated neck lift procedures with excellent aesthetic outcomes and minimal complications.
Keywords: cervicoplasty; rhytidectomy; face lift; plastic surgery; neck; platysmaplasty